2018
DOI: 10.1097/cad.0000000000000611
|View full text |Cite
|
Sign up to set email alerts
|

A novel penicillin derivative induces antitumor effect in melanoma cells

Abstract: In this study, we explored the in-vitro and in-vivo mechanism of antitumor action of a novel synthetic nonantibiotic triazolylpeptidyl penicillin derivative, named TAP7f, on B16-F0 murine melanoma cells. In-vitro assays showed that TAP7f caused an inhibition of S phase progression and a concomitant decrease of the percentage of cells in G0/G1 phase. We also found that TAP7f treatment induced an apoptotic response characterized by an increase of the sub-G1 fraction of B16-F0 hypodiploid cells, the occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In a previous work, we have examined the in vitro antitumor action of the non-antibiotic triazolyl penicillin derivative TAP7f in different non metastatic human and murine adenocarcinoma cell lines (Blank et al, 2018). We also demonstrated the in vivo efficacy of this derivative in a murine melanoma model (Blank et al, 2018). In this work, we reported for the first time the anti-metastatic properties of TAP7f against highly metastatic melanoma cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…In a previous work, we have examined the in vitro antitumor action of the non-antibiotic triazolyl penicillin derivative TAP7f in different non metastatic human and murine adenocarcinoma cell lines (Blank et al, 2018). We also demonstrated the in vivo efficacy of this derivative in a murine melanoma model (Blank et al, 2018). In this work, we reported for the first time the anti-metastatic properties of TAP7f against highly metastatic melanoma cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 76%
“…We have also demonstrated that TAP7f induced an antitumor effect through the induction of cell cycle arrest and the activation of both death receptor and mitochondria-dependent apoptotic pathways in melanoma B16-F0 cells (Blank et al, 2018). Moreover, when TAP7f was evaluated in vivo in a B16-F0 murine melanoma model, results showed a reduction of approximately 70% of tumor growth (Blank et al, 2018). In order to continue exploring TAP7f biological properties, we herein investigated the in vitro antimetastatic effect of this compound in murine B16-F10 and human A375 melanoma cells.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations